The complete adventures of Huckleberry Finn and Tom Sawyer - Twain, Mark, 1835-1910 (E-artnow, 2013)
Huckleberry "Huck" Finn is a fictional character created by Mark Twain, who first appeared in the book The Adventures of Tom Sawyer and is the protagonist and narrator of its sequel, Adventures of Huckleberry Finn. He is 12 or 13 years old during the former and a year older ("thirteen or fourteen or along there," Chapter 17) at the time of the latter. Huck also narrates Tom Sawyer Abroad and Tom Sawyer, Detective, two shorter sequels to the first two books. This carefully crafted ebook is formatted for your eReader with a functional and detailed table of contents and the following works: The Adventures of Tom Sawyer, The Adventures of Huckleberry Finn, Tom Sawyer Abroad, Tom Sawyer, Detective.